Indigenous knowledge, language and sustainability: insights from the Baram and Kumal communities in Gorkha, Nepal - Sherpa, Pasang (Nepal Sociological Journal, 2025)
This paper explores the Indigenous knowledge, cultural values, and sustainability through the experiences of the Baram and Kumal peoples in Gorkha, Nepal. It examines how their languages, customary practices, and cultural values inform ecological governance, sustainable resource management, and community solidarity. These Indigenous knowledge systems are deeply embedded in language, rituals, and oral traditions, and reflect principles of reciprocity, cooperation, and collective responsibility that sustain both society and environment. Practices such as Parma (labor exchange) and customary forest management demonstrate how cultural values shape sustainable livelihoods. However, state policies, economic changes, and dominant socio-cultural forces such as Hinduization, Sanskritization, and formal education systems have marginalized these knowledge systems, threatening linguistic diversity and traditional ecological practices. Language, as a key repository of Indigenous epistemologies, plays a critical role in shaping concepts of sustainability and environmental ethics. The erosion of the Baram and Kumal languages due to modernization and assimilationist policies risks the loss of invaluable cultural and ecological knowledge. By centering Indigenous perspectives, this paper underscores the need to recognize, protect, and revitalize Indigenous languages and knowledge systems as essential to sustainable development and social equity. It highlights the interdependence between cultural identity, language, and environmental stewardship in the ongoing struggle for Indigenous survival and sustainability.